The history of swimming resarch - Pelayo, P.; Alberty, M. (World book of swimming: From science to performance, 2012)
The idea for this book arose from discussions with students and staff at the Centre For Sports and Exercise Science at the University of Essex. l particulary thank Jerry Shearman, Martin Sellens, and Mike Wilson who encouraged me to think of applying my biomechanical ideas to sports science. I am also grateful for the support of the many scientist - at Essex and elsewhere - who suggested helpful improvements to the content of this book. These include Ralph Beneke, Yagesh Bhambani, Stephen Harrlige, Gareth Montgomery, Ceri Nicholas, Peter Rasmussen, Kevin Tipton, Niels Vollaard, Anna Wittekind and John Wyatt.